Synthesis, Crystal Packing, and Ambipolar Carrier Transport Property of Twisted Dibenzo[g, p]chrysenes. Issue 6 (24th April 2014) - Ueda, Yasuyuki; Tsuji, Hayato; Tanaka, Hideyuki; Nakamura, Eiichi
Abstract A versatile method for the synthesis of dibenzo[g, p]chrysene (DBC) derivatives based on regio‐ and stereoselective stannyllithiation to diarylacetylenes is described. This method affords a variety of DBCs possessing both electron‐donating and electron‐withdrawing functional groups. These twisted molecules take brickwork packing structures in single crystals. Thus, ambipolar carrier transport properties with mobility values of up to 10−3 cm2 V−1 s−1 in the amorphous state were achieved. Functional groups on DBC frameworks are considered to increase carrier mobility through the enhancement of intermolecular interactions in the brickwork packing structures.